ANALYSIS OF AIR TRAFFIC IN EUROPEAN REGION - Luppo, Alexander; Hlushko, Oksana; Dolmatova, Darya (Proceedings of National Aviation University (archive), 2013)
Was provided analysis of current air traffic, considered possible developments in air traffic, studied long-term forecast of air traffic growth in European region.